2023
DOI: 10.1007/s40265-023-01864-x
|View full text |Cite|
|
Sign up to set email alerts
|

Sparsentan: First Approval

Abstract: Sparsentan (FILSPARI™) is an oral, dual endothelin angiotensin receptor antagonist that is being developed by Travere Therapeutics for the treatment of immunoglobulin A (IgA) nephropathy and focal segmental glomerulosclerosis (FSGS). In February 2023, sparsentan received accelerated approval in the USA for reducing proteinuria in adults with primary IgA nephropathy who are at risk of rapid disease progression. This article summarizes the milestones in the development of sparsentan leading to this first approva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The anticancer drug kinase inhibitors quizartinib and tivozanib have been covered in earlier sections. Sparsentan (approved 2/2023) is a first-in-class medication for patients suffering from focal segmental glomerulo­sclerosis (FSGS). In addition to the isoxazole, sparsentan is also decorated with an unusual oxidized spiro-imidazole nitrogen heterocycle.…”
Section: Us Fda-approved Nitrogen-containing Drugs (January 2013–dece...mentioning
confidence: 99%
“…The anticancer drug kinase inhibitors quizartinib and tivozanib have been covered in earlier sections. Sparsentan (approved 2/2023) is a first-in-class medication for patients suffering from focal segmental glomerulo­sclerosis (FSGS). In addition to the isoxazole, sparsentan is also decorated with an unusual oxidized spiro-imidazole nitrogen heterocycle.…”
Section: Us Fda-approved Nitrogen-containing Drugs (January 2013–dece...mentioning
confidence: 99%
“…Sparsentan (RE-021, PS433540, DARA-a) is a first-in-class, orally active, dual-acting, selective antagonist of the AT1 receptor and the endothelin type A (ET A ) receptor [ 44 ]. This compound has been in development for the treatment of focal segmental glomerulosclerosis, IgA nephropathy, and other kidney-related conditions [ 45 , 46 , 47 ]. In focal segmental glomerulosclerosis, certain segments of some glomeruli become scarred and damaged, leading to a decrease in their filtering function.…”
Section: Sparsentan (N-(4-((5-(4-(2-carboxyethyl)-1-piperazinyl)-2-me...mentioning
confidence: 99%
“…Data from the PROTECT study indicated that after 9 months of treatment, sparsentan was able to reduce the urine protein to creatinine ratio (UPCR) to a significantly greater extent than the ARB irbesartan, although long-term data are needed to ascertain whether this translates to long-term renoprotection [103]. The overall safety profile of sparsentan was similar to that of irbesartan, although higher rates of peripheral edema, hypotension, dizziness, and anemia were observed [102,103].…”
Section: Symptom Reduction and Supportive Carementioning
confidence: 99%
“…The second drug approved by the FDA for the treatment of IgAN was the dual en dothelin angiotensin-receptor antagonist sparsentan, which is also indicated for the re duction in proteinuria in adults with primary IgAN at risk of rapid disease progressio [102]. Data from the PROTECT study indicated that after 9 months of treatmen sparsentan was able to reduce the urine protein to creatinine ratio (UPCR) to a signif cantly greater extent than the ARB irbesartan, although long-term data are needed to as certain whether this translates to long-term renoprotection [103].…”
Section: Targeted Treatmentsmentioning
confidence: 99%